1997
DOI: 10.1177/002215549704500402
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Expression of Bone Matrix Proteins During Rat Calvaria Osteoblast Differentiation and Bone Nodule Formation In Vitro

Abstract: We investigated the expression of osteocalcin (OC), bone sialoprotein (BSP), osteonectin (ON), and alkaline phosphatase (ALP) during cell differentiation and bone nodule formation by fetal rat calvaria cells, using immunofluorescent and immunogold techniques at light and electron microscopic levels. Six hours after plating all proteins were expressed in calvaria cells. However, expression was not detected during the proliferation phase after plating. Cell morphological modifications were observed in osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 61 publications
7
75
0
8
Order By: Relevance
“…ALP gene expression was significantly depressed, whereas OC was increased from stage 2 to 3 (Owen et al, 1990). This formulation is supported by several osteogenesis studies (Harris et al, 1994;Nefussi et al, 1997;Yamamoto et al, 2002;Yamamoto et al, 2003;Siggelkow et al, 2004). The ALP and OC mRNA expression patterns in DFAT cells in the present study were very similar to their reports.…”
Section: Discussionsupporting
confidence: 91%
“…ALP gene expression was significantly depressed, whereas OC was increased from stage 2 to 3 (Owen et al, 1990). This formulation is supported by several osteogenesis studies (Harris et al, 1994;Nefussi et al, 1997;Yamamoto et al, 2002;Yamamoto et al, 2003;Siggelkow et al, 2004). The ALP and OC mRNA expression patterns in DFAT cells in the present study were very similar to their reports.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro osteogenic differentiation of primary osteoblasts [8][9][10][11][12][13]44] and ESCs [17][18][19][20][21] have both been well described, but there have been few comparative studies. In this study, both cell types showed expression of markers indicative of osteogenic differentiation and formed nodules comprising Values corrected to proportion of osteogenic control.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM deposited by osteoblasts in vitro has been shown to include collagen-I (col-I), fibronectin, osteocalcin (OCN), and osteopontin (OPN), and staining for these proteins is often most predominant around the mineralized nodules [10][11][12][13]. The process of osteogenesis is coordinated by various transcription factors, with Runx2 and osterix being regarded as key regulators [14][15][16].…”
mentioning
confidence: 99%
“…For the osteoblasts, osteoid matrix, mineralized matrix and chondroblasts there was an increase in the protein with strongly positive labeling. The increase in BSP expression, after disjunction, may be justified by the fact that this protein participates in the process of cell differentiation and activities, as well as maturation and mineralization of the bone matrix [13,38].…”
Section: International Journal Of Dental Sciences and Researchmentioning
confidence: 99%
“…The main noncollagenous bone matrix proteins are osteonectin (ONC), osteopontin (OPN), bone sialoprotein (BSP) and osteocalcin (OCC). The functions of these proteins are related to the regulation of mineralization of collagen fibers and modulation of the division, migration, differentiation and maturation of bone cells and are synthesized in different stages of osteogenesis [13].…”
Section: Introductionmentioning
confidence: 99%